Investigation on the strength of expanded clay aggregate concrete specimens after thermal exposure - Danguolė Plungytė; Ričardas Plungė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The article describes the results of a laboratory study of the properties of expanded clay blocks. Expanded clay concrete modular blocks are used to install chimney stacks. The research aims to determine how the physical-mechanical properties of the material change when they are exposed to high temperatures. The question is raised about how much the strength of the structural material can decrease if it is exposed to higher temperatures. To broader and more objectively determine the material properties, materials with different fillers were chosen for the sample blocks. 24 expanded clay concrete blocks were formed for the study. The samples were hardened under uniform conditions in the laboratory. After the anticipated hardening time, the weight of the samples was determined, and they were weighed again after thermal exposure. Having adjusted the mass of expanded clay samples, their compressive strength properties were investigated. The research was carried out in the KUT Building Materials Laboratory following the requirements for compressive strength established in the normative documents. After comparing the changes in the weight of expanded clay concrete sample blocks before and after thermal effects, the obtained results showed that the weight of the samples with coarse expanded clay filler and fibre decreased significantly after temperature exposure at 105 °C. After exposure of the same samples to temperatures of 300 °C and 600 °C, their mass decreased even more. Before performing the compressive strength test of expanded clay concrete samples, all sample cubes were numbered and divided into three groups after thermal exposure. To compare the research results, control samples were separated from each group of foamed cubes with different fillings. The results of the compressive strength of the control samples were compared with the results of the thermally affected samples. The research revealed that the samples with fine-grained filler retained the highest strength after exposure to high temperatures, while the strength results of all other samples with coarse filler and coarse filler with fibre were low. The comparison of the results of the compressive strength of expanded clay concrete samples with coarse fillers suggests that the samples with fibre remained stronger after exposure to high temperature (600 °C) than the samples without additives. To sum up the results of the laboratory test of expanded clay concrete samples, it can be assumed that their strength may decrease by up to 38 per cent when exposed to expanded clay concrete at high temperatures for a longer period.